Pengaruh Pemberdayaan dan Kepuasan Kerja Terhadap Komitmen Organisasional Pada PT. Nusantara Sakti Gorontalo - Idris, Zulkarnain Ilyas; Jusup, Sri Meike (Universitas muhammadiyah palembang, 2023)
A good organization certainly pays attention to the condition of employees, so that employees will have good commitment and in the end there will be a sense of satisfaction. This study aims to determine the effect of empowerment and job satisfaction on organizational commitment at PT. Nusantara Sakti Gorontalo both partially and simultaneously. The population and sample in this study are employees of PT. Nusantara Sakti with a total of 34 people uses a saturated sampling technique where all samples are used as a population. The analytical method used is multiple regression analysis. The results showed that both simultaneously and partially empowerment and job satisfaction have a positive and significant impact on organizational commitment at PT. Nusantara Sakti Gorontalo